A Systematic Review on Interventions Supporting Preceptor Development. Issue 6 (November 2015) - Windey, Maryann; Lawrence, Carol; Guthrie, Kimberly; Weeks, Debra; Sullo, Elaine; Chapa, Deborah W.
Abstract : Increases in newly licensed nurses and experienced nurses changing specialties create a challenge for nursing professional development specialists (NPDS). The NPDS must use the best available evidence in designing programs. A systematic review of interventions for developing preceptors is needed to inform the NPDS in best practice. A search was conducted for full-text, quantitative, and mixed-methods articles published after the year 2000. Over 4000 titles were initially identified, which yielded 12 research studies for evaluation and syntheses. Results identified a limited body of evidence reflecting a need for NPDS to increase efforts in measuring the effectiveness of preceptor development initiatives. (See CE Video, Supplemental Digital Content 1, http://links.lww.com/JNPD/A9 )